Sustainable infrastructure : sustainable buildings - Green, Elisabeth; Hope, Tristram; Yates, Alan (ICE Publishing, 2015)
This is an indispensable handbook that combines a summary of good practice and sources of information helpful to practitioners involved in the design and procurement of buildings. This book illustrates the need for inter-disciplinary integration and an understanding of environmental physics as early as possible in the design process in order to deliver high-quality, economical and sustainable infrastructure across the globe. With many years of knowledge related to the sustainability of buildings, the authors aim to provide a balanced view of current best practice and a vision of the way forward in a rapidly changing sector, the demands placed on its outputs and the solutions that are available. -- Provided by publisher.
Keywords: Sustainable buildings -- Design and construction.; Sustainable architecture.; elektronické knihy; electronic books